Object narratives as a methodology for mitigating marine plastic pollution: multidisciplinary investigations in Galápagos. (February 2020) - Schofield, John; Wyles, Kayleigh J.; Doherty, Sean; Donnelly, Andy; Jones, Jen; Porter, Adam
Abstract: Abstract : Marine plastic pollution is a global environmental concern. With reference to approaches in contemporary archaeology, object biographies and psychology, this article presents the application of a novel participatory ('World Café') methodology that aims both to understand how marine plastic pollution occurs and to demonstrate the value of the approach for encouraging behaviour change. As proof of concept, the authors present the preliminary results of fieldwork involving local people in the Galápagos archipelago to demonstrate the benefits of an archaeological approach in developing new frameworks to help mitigate this critical environmental threat.